2004
DOI: 10.1590/s0100-879x2004001100017
|View full text |Cite
|
Sign up to set email alerts
|

Social disability of Brazilian mood disorder patients

Abstract: Mood disorders cause many social problems, often involving family relationships. Few studies are available in the literature comparing patients with bipolar, unipolar, dysthymic, and double depressive disorders concerning these aspects. In the present study, demographic and disease data were collected using a specifically prepared questionnaire. Social adjustment was assessed using the Disability Adjustment Scale and family relationships were evaluated using the Global Assessment of Relational Functioning Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
1
0
0
1
Order By: Relevance
“…In the general panorama of cognitive aspects, our results corroborate the results of existing studies. Compared to the HC group, BD patients in the episodic group had fewer years of schooling, even though their average was equivalent to that corresponding to the end of high school, corroborating both Brazilian data ( Tucci et al, 2004 ; Ponsoni et al, 2021 ), and those from other countries ( Torres et al, 2020 ). This suggested that BD presents itself as a condition that affects education in countries like Brazil.…”
Section: Discussionsupporting
confidence: 82%
“…In the general panorama of cognitive aspects, our results corroborate the results of existing studies. Compared to the HC group, BD patients in the episodic group had fewer years of schooling, even though their average was equivalent to that corresponding to the end of high school, corroborating both Brazilian data ( Tucci et al, 2004 ; Ponsoni et al, 2021 ), and those from other countries ( Torres et al, 2020 ). This suggested that BD presents itself as a condition that affects education in countries like Brazil.…”
Section: Discussionsupporting
confidence: 82%
“…As necessidades de cuidados dessas pessoas podem se estender por muitos anos, já que este distúrbio tende a ter seu início entre as idades de 16 e 30 anos, e em geral, persiste ao longo da vida (Mueser, 2004;Rössler et al 2005). Outros transtornos psicóticos, como o transtorno afetivo bipolar e a depressão com sintomas psicóticos, também costumam afetar seriamente as pessoas em seu funcionamento social gerando necessidades de cuidados em várias áreas (Morgan, 2005;Tucci, 2004).…”
Section: Introductionunclassified